Pharmacological investigation on alpha-asarone in experimental model of nicotine withdrawal induced depression in mice / Ranjith Kumar Chellian - Ranjith Kumar, Chellian (2018)
Depression is one of the major withdrawal symptoms during smoking cessation. The cAMP response element protein binding (CREB) and brain-derived neurotrophic factor (BDNF) signalling pathways have been implicated in the neuroplasticity during nicotinewithdrawal in mice. Traditionally, Acorus calamus Linn (Acoraceae) rhizomes were used to discontinue the habit of smoking cigarettes. Alpha-asarone is one of the bioactive phytochemicals present in the rhizomes of Acorus calamus Linn and possesses an antidepressant-like activity in ICR mice. In addition, α-asarone was shown to interact with CREB and BDNF pathways. Hence, it is hypothesized that α-asarone could be effective in alleviating depression-like behaviour during nicotine-withdrawal in mice. In this study, the dose-dependent effect of α-asarone in the tail suspension test and locomotor activity in ICR mice was studied. In addition, the possible monoaminergic mechanism(s) involved in the antidepressant effect of α-asarone was studied in alphamethyl-para-tyrosine (AMPT, a catecholamine synthesis inhibitor) and 4-chloro-DLphenylalanine (PCPA, a serotonin synthesis inhibitor) pre-treated ICR mice, respectively, using tail suspension test. In a separate study, the effect of α-asarone or bupropion on nicotine-induced hypomotility and hypothermia in ICR mice was investigated. In the nicotine-withdrawal study, the effect of repeated α-asarone or bupropion treatment in naïve and nicotine-withdrawn C57BL6 mice was studied in forced swim test and spontaneous locomotor activity test. In addition, the effects of repeated α-asarone or bupropion treatment on the hippocampal CREB, phosphorylated-CREB (pCREB), and BDNF levels in nicotine-withdrawn C57BL6 mice were measured. iv The study results showed that the acute treatment of α-asarone at lower doses (15 and 20 mg/kg, i.p.) significantly decreased the duration of immobility time in the tail suspension test. Moreover, AMPT and PCPA pre-treatment significantly reversed the anti-immobility effect of α-asarone (20 mg/kg, i.p.) in the tail suspension test. The effect of α-asarone on nicotine’s pharmacological effect revealed that the α-asarone (5, 10, 20 and 30 mg/kg, i.p.) did not reverse or block the nicotine-induced hypomotility and hypothermia in mice. However, bupropion (20 mg/kg, i.p.) significantly reversed the nicotine-induced hypomotility and hypothermia in mice. In the nicotine-withdrawal study, the immobility time of nicotine-withdrawn mice was significantly attenuated with repeated α-asarone (5, 10 and 20 mg/kg, i.p. × 8 days) or bupropion (10 mg/kg, i.p. × 8 days) pretreatment in the forced swim test. However, repeated α-asarone and bupropion treatment did not significantly alter the immobility time in the forced swim test or spontaneous locomotor activity in naïve mice. In addition, repeated α-asarone or bupropion pre-treatment significantly attenuated the hippocampal pCREB levels in nicotine-withdrawn mice. Taken together, these results suggest that α-asarone possess an antidepressant-like activity only at lower doses through its interaction with noradrenergic, dopaminergic and serotonergic systems in ICR mice. Furthermore, unlike bupropion, α-asarone was not capable of interacting with nicotinic acetylcholine receptors. Besides, α-asarone treatment attenuated the nicotine-withdrawal induced depression-like behaviour through the modulation of hippocampal pCREB levels in nicotine-withdrawn C57BL6 mice. Therefore, α-asarone may have a place in the treatment of depression upon cessation of nicotine-containing products mainly in the form of cigarettes.